Pengaruh Gaya Mengajar Latihan Terhadap Hasil Belajar Keterampilan Servis Bawah Pada Permainan Bola Voli - M. Ilham Prasetia; Eduard E. Kumenap; Yuliana Sattu (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The problem in this research is whether the teaching style of training has an influence on the learning outcomes of bottom serve skills in the volleyball game of students at SMP Negeri 3 Tondano. This study aims to determine the average score of learning outcomes for lower serve skills in the experimental group's volleyball game which was taught using a high practice teaching style compared to the average score of learning outcomes of lower serve skills in the control group's volleyball game which was not taught using this teaching style. exercise. The research method used is an experimental research method. The population in this study was all students in class VIII of SMP Negeri 3 Tondano, totaling 46 people. The sample in this study consisted of 20 people taken randomly. The results of this analysis proved that there were significant differences between the two groups. Where the average learning outcomes for lower serve skills in the volleyball game of students at SMP Negeri 3 Tondano in the group taught with the Practice teaching style were better than the control group who did not receive treatment.